2015
DOI: 10.1111/cge.12590
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease and enzyme replacement therapy in classic patients with same mutation: different formulations – different outcome?

Abstract: We describe the results of the multidisciplinary evaluation in patients with Fabry disease and the same genetic mutation and their outcomes using different approved enzyme replacement therapy (ERT). We measured baseline data and serial results of neuropathic pain assessment and renal, cardiac and cerebrovascular functioning. Pain scale showed improvement in all male cases treated with agalsidasa beta. A mild improvement was detected in agalsidasa alfa-treated patients after 1 year with posterior increase. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…There is some indirect evidence from dose‐switching studies that suggests that ERT dose may be of relevance for pain outcomes, at least in the short term. At 1‐year follow‐up, there was improvement or stabilization of pain symptoms in patients who continued treatment with agalsidase beta, but an increase in pain when patients receiving agalsidase beta were transferred to treatment with agalsidase alfa . In a different study, patients who switched from agalsidase beta 1.0 mg/kg to a lower dose or to agalsidase alfa 0.2 mg/kg reported an increase in pain attacks, chronic pain, gastrointestinal pain, and diarrhea compared with those who continued receiving agalsidase beta 1.0 mg/kg after 1 year .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There is some indirect evidence from dose‐switching studies that suggests that ERT dose may be of relevance for pain outcomes, at least in the short term. At 1‐year follow‐up, there was improvement or stabilization of pain symptoms in patients who continued treatment with agalsidase beta, but an increase in pain when patients receiving agalsidase beta were transferred to treatment with agalsidase alfa . In a different study, patients who switched from agalsidase beta 1.0 mg/kg to a lower dose or to agalsidase alfa 0.2 mg/kg reported an increase in pain attacks, chronic pain, gastrointestinal pain, and diarrhea compared with those who continued receiving agalsidase beta 1.0 mg/kg after 1 year .…”
Section: Resultsmentioning
confidence: 97%
“…In terms of small nerve fiber sensory function, a study of 22 patients with FD revealed improved thermal perception and vibration detection thresholds with agalsidase beta . Although ERT reduces pain outcomes in a variety of Fabry‐related pain conditions, pain does not always completely resolve , explaining the need for adjunctive medications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cases of nephropathy only, classic type, and an atypical variant have been reported [8,25,26]. In addition, Politei et al revealed that patients with the same mutation as the current case (L415P) show different organ damage [27]. These findings suggest that gene mutation is not the only factor involved in organ damage.…”
Section: Gene Mutation and Lyonizationmentioning
confidence: 64%
“…Ambas están compuestas por la misma cadena de aminoácidos, es decir, son la misma proteína humana. La diferencia reside en la dosis aprobada (agalsidasa beta 1 mg/kg de peso y agalsidasa alfa 0,2mg/kg) y en la cantidad de residuos de manosa 6-fosfato (agalsidasa beta 3,6mol/mol de proteína y agalsidasa alfa 1,3mol/mol de proteína) 3,9,68 . Su principal mecanismo de acción es la sustitución de la enzima alfa-galactosidasa A, posibilitando la hidrólisis del Gb3 y liso-Gb3 al separar un residuo de galactosa terminal de la molécula, disminuyendo así su acumulación en los tejidos 2,9 .…”
Section: Tratamientounclassified
“…La presencia de mayor cantidad de residuos de manosa 6 -fosfato produce un mejor reconocimiento por los receptores de manosa 6 -fosfato de la membrana celular y consecuentemente mayor internalización celular de la enzima 9,66 . De acuerdo con los estudios publicados, pareciera que el beneficio tisular y clínico tiene relación directa con la dosis de TRE utilizada 9,[67][68][69][70][71][72] . Distintos protocolos han demostrado que el uso de agalsidasa beta a dosis de 1mg/kg cada 14 días produce remoción total de Gb3 de los podocitos renales en comparación con la agalsidasa alfa a dosis de 0,2mg/kg9,70-72.…”
Section: Tratamientounclassified